Sustainable Rural Development or (Sustainable) Rural Livelihoods? Strategies for the 21st Century in Peripheral Regions - Bogumiła Lisocka-Jaegermann (Barometr Regionalny, 2015)
Ongoing discussions concerning the concept of development applied within the context of peripheral regions (including rural development, regional development, sustainable development, local development, etc.), and particularly its critical deconstruction, encourage us to look for new theoretical approaches and terminological constructs that would be useful in research and design of desired changes taking place in rural areas and that could substitute the contested notion of “development.” The text discusses strengths and weaknesses of “sustainable rural livelihood” — as a concept, as well as a framework of academic analysis and action — in the context of its application within “rural development” studies.